2005
DOI: 10.1128/jvi.79.3.1367-1378.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to Apo2 Ligand (Apo2L)/Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL)-Mediated Apoptosis and Constitutive Expression of Apo2L/TRAIL in Human T-Cell Leukemia Virus Type 1-Infected T-Cell Lines

Abstract: Adult T-cell leukemia (ATL), a CD4؉ -T-cell malignancy caused by human T-cell leukemia virus type 1 (HTLV-1), is difficult to cure, and novel treatments are urgently needed. Apo2 ligand (Apo2L; also tumor necrosis factor-related apoptosis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…We were interested in the activity of the M22 Tax mutant since Tax transactivates survival genes including Bcl-xL by NF-kB activation, thereby protecting cells from apoptosis induced by other agents such as IL-2 or Apo-2 (Tsukahara et al, 1999;Matsuda et al, 2005). To investigate whether Tax could attenuate p53-independent apoptosis through its transcriptional activities, HCT-116 p53 knockout cells transiently expressing wild-type or mutant Tax proteins were irradiated and fixed with 1% formaldehyde and 70% ethanol 24 h Tax/Chk2 interaction attenuates the DNA-damage-induced apoptosis HU Park et al post-g-IR followed by TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested in the activity of the M22 Tax mutant since Tax transactivates survival genes including Bcl-xL by NF-kB activation, thereby protecting cells from apoptosis induced by other agents such as IL-2 or Apo-2 (Tsukahara et al, 1999;Matsuda et al, 2005). To investigate whether Tax could attenuate p53-independent apoptosis through its transcriptional activities, HCT-116 p53 knockout cells transiently expressing wild-type or mutant Tax proteins were irradiated and fixed with 1% formaldehyde and 70% ethanol 24 h Tax/Chk2 interaction attenuates the DNA-damage-induced apoptosis HU Park et al post-g-IR followed by TUNEL assay.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support that Chk2 does not regulate G 2 accumulation but apoptosis in response to DNA damage. Recent studies have shown that HTLV-1 Tax protects cells from apoptosis induced by activation of cell surface markers such as IL-2 or Apo-2 receptors (Tsukahara et al, 1999;Matsuda et al, 2005). Protection is dependent upon the ability of Tax to activate the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Kaposi sarcomaassociated human herpesvirus 8 and related gammaherpesviruses prevent the triggering of TRAIL-induced apoptosis by encoding viral FLICE-inhibitory proteins (vFLIPs) that interact with the Fas-associated death domain (FADD) to inhibit active caspase 8 generation (34). Additionally, T cells infected with human-T cell leukemia virus type 1 are resistant to TRAIL-mediated apoptosis by the viral transactivator Tax (35). Furthermore, three proteins (E3 RID) encoded by the human adenovirus type 5 induce the internalization of TRAIL receptors from the cell surface targeting lysosomal degradation (36).…”
Section: Discussionmentioning
confidence: 99%
“…NFκB also upregulates FasL and together, these proapoptotic ligands may be responsible for tumor-cell elimination in immune surveillance and/or attenuation of T-cell activation to prevent autoimmunity. NFκB is also responsible for constitutive TRAIL expression in human T-cell leukemia virus type I (HTLV-1)-induced leukemia, though other concomitant effects of NFκB seem to cause resistance to TRAIL-mediated apoptosis 64 . In accordance with a positive regulatory role for NFκB with respect to the TRAIL gene, the prostaglandin 15d-PGJ2 represses TRAIL gene transcription by inhibiting the binding of NFκB to the NFκB binding site 1 (Fig.…”
Section: Regulation Of the Human Trail Genementioning
confidence: 99%